2014
DOI: 10.1093/nar/gku451
|View full text |Cite
|
Sign up to set email alerts
|

SPIB and BATF provide alternate determinants of IRF4 occupancy in diffuse large B-cell lymphoma linked to disease heterogeneity

Abstract: Interferon regulatory factor 4 (IRF4) is central to the transcriptional network of activated B-cell-like diffuse large B-cell lymphoma (ABC-DLBCL), an aggressive lymphoma subgroup defined by gene expression profiling. Since cofactor association modifies transcriptional regulatory input by IRF4, we assessed genome occupancy by IRF4 and endogenous cofactors in ABC-DLBCL cell lines. IRF4 partners with SPIB, PU.1 and BATF genome-wide, but SPIB provides the dominant IRF4 partner in this context. Upon SPIB knockdown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 78 publications
4
51
0
Order By: Relevance
“…Thus, disrupting IRF4 activity is toxic to ABC DLBCLs due to the collapse of both pro-survival NF-κB signaling and suicide by autocrine induction of interferon [15]. Finally, IRF4 has been found to have an additional binding partner in lymphocytes, BATF, which can influence the spectrum of genes targeted during activation and differentiation [17, 18]. IRF4 and BATF are required downstream of BCR signaling to promote transcriptional programs during GC formation [17].…”
Section: Transcriptional Feedbackmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, disrupting IRF4 activity is toxic to ABC DLBCLs due to the collapse of both pro-survival NF-κB signaling and suicide by autocrine induction of interferon [15]. Finally, IRF4 has been found to have an additional binding partner in lymphocytes, BATF, which can influence the spectrum of genes targeted during activation and differentiation [17, 18]. IRF4 and BATF are required downstream of BCR signaling to promote transcriptional programs during GC formation [17].…”
Section: Transcriptional Feedbackmentioning
confidence: 99%
“…IRF4 and BATF are required downstream of BCR signaling to promote transcriptional programs during GC formation [17]. The association of IRF4 with SPIB versus BATF generates heterodimeric transcription factors that control distinct and developmentally-related gene expression programs in DLBCL, and they can been used to identify a subset of ABC DLBCL patients (SPIB-high/BATF-low) with MYD88 L265P who may have a better clinical outcome [18]. Thus, oncogenic signaling downstream of the BCR creates multiple self-reinforcing survival signals through the amplification of various NF-κB transcriptional networks in ABC DLBCL.…”
Section: Transcriptional Feedbackmentioning
confidence: 99%
“…It has been found that REEP1 could facilitate mitochondrial‐ER interactions, which may result in intracellular Ca 2+ overload and axonal damage, and REEP1 variants were recognized as causes of Neurological Disease like hereditary spastic paraplegia (HSP) and distal hereditary motor neuropathy (dHMN) . The third gene SPIB, encoding an ETS‐domain transcription factor, was believed to be associated with cancers especially in lymphomas . Also, Yi‐Jung et al found the SPIB may be involved in tumorigenesis in live cancer, and Wei et al reported that SPIB is expressed in invasive cancer cells in human primary lung cancer tissues.…”
Section: Discussionmentioning
confidence: 99%
“…37 The third gene SPIB, encoding an ETS-domain transcription factor, was believed to be associated with cancers especially in lymphomas. 38,39 Also, Yi-Jung et al 40 found the SPIB may be involved in tumorigenesis in live cancer, and Wei et al 41 reported that SPIB is expressed in invasive cancer cells in human primary lung cancer tissues. ALDH3B2 was widely known as a member of aldehyde dehydrogenases (ALDHs).…”
Section: Discussionmentioning
confidence: 99%
“…To establish OSdlbcl web server, we downloaded one TCGA cohort and six GEO cohorts with gene expression profiles and clinical follow-up information ( Table 1). [15][16][17][18][19][20][21][22][23] A total of 1100 unique DLBCL cases were collected, all of which have available gene expression profiling data and clinical followup survival information. Overall survival (OS) is the most important endpoint for the clinical outcomes in OSdlbcl.…”
Section: Clinical Characteristics Of Dlbcl Datasets Used In Osdlbclmentioning
confidence: 99%